Dukungan Sosial, Kecerdasan Emosi Dan Resiliensi Guru Sekolah Luar Biasa - ., Maisyarah (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2015)
Abstract. This study aims to determine whether there is a relationship betweensocial support, emotional intelligence with resilience teachers of extraordinaryschools (SLB) in Surabaya .this study conducted on teachers who teach inextraordinary schools by the number of study subjects were 100 people who are inifive schools. Collection data in the form of social support scala consisting of 26item, emotional intelligence of 20 items and teacher resilience 26 item. That measureinstruments have valid and reliabilitas. Data were analyzed using multiple regresionanalysis. The result of multiple regression analysis showed that variables of socialsupport, emotional intelligence have a significant relation with resilience(F=50.893; p=0,000). This suggests that there is a positive and signifikactcorrelation between social support and emotional intelligence with resilience ofteacher. From the result of calculation for each variables to the resilience, it’sknown that emotional intelligence (0,239%) more contributes to resilience thansocial support(0,562%).Keywords : social support, emotional intelligence, resilience